Transportation Path Optimization of Modern Logistics Distribution considering Hybrid Tabu Search Algorithm. (7th September 2021) - Guo, Jinjin; Zhang, Huiying; Sun, Guie
Abstract : The optimization of transportation path for distribution vehicles, which is about the mixed tabu search method, can not only reduce the cost but also improve the optimization of the vehicle transportation path. This algorithm first studies the current situation of the logistics distribution vehicle transportation path and then uses the hybrid tabu search method to calculate the vehicle transportation path. According to the real case analysis, it can be proved that the hybrid tabu search calculation method can improve the efficiency, the proposed modern logistics distribution vehicle transportation path is also the best method, and the transportation cost is greatly reduced.